Analysis of Students' Social Care Attitudes towards the Increase in Criminal Acts of Motor Vehicle Theft in Jambi Outer City District (Study of Students from the Civics Study Program at Jambi University) - Reska, Tio Fadila; Usmanto, Heri; Melisa, Melisa (CV. Rayyan Dwi Bharata, 2024)
Motor vehicle thefts which always occur in Mendalo Indah Village, Jambi Luar Kota District, cause anxiety in the community. This condition requires attention and action from various parties, including students. Students of the Pancasila and Citizenship Education Study Program (PPKn) are expected to have a high level of social care and be able to contribute to preventing and overcoming this problem. This research aims to find out the social care attitude of PPKn students towards the widespread crime of motor vehicle theft in Mendalo Indah Village, Jambi Luar Kota District. This research method is a type of qualitative descriptive data research. Information is obtained through observation, interviews and documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation and data verification. The results of this research can be concluded that the social care attitude of PPKn students still needs a lot of improvement, their empathetic and caring behavior, especially in sharing loss information on social media, is a strength that needs to be appreciated. Greater efforts are needed to increase awareness, active participation and cooperation of students in efforts to prevent and overcome motor vehicle theft, by utilizing the existing basis of empathy to build a safer and more harmonious environment.